Specific Aspects Of The Methodology For Using Cloud Technologies In Virtual Education - Shukurov Akmal Uktamovich (Genius Publishing Group, 2022)
The implementation of the content of disciplines related to Virtual technologies is based on the selection of educational tasks, in accordance with ideas that rely on the understanding of the territory of close development and contextual education. With the help of cloud technologies, the choice of content for teaching disciplines related to information technology is carried out in accordance with educational goals and on the basis of the selection of Highlighted Content
Keywords: Virtual; Virtual Learning; Cloud; Google Chrome